La República Dominicana en 2030 hacia una nación cohesionada - Godínez Z., Víctor Manuel (Godínez Zúñiga); Máttar, Jorge (Libros de la CEPAL ;, 2009)
"This book ... analyzes the challenges that the Dominican Republic now confronts. Starting from an assessment of the present situation, the outlook for the next quarter century is examined in each chapter. The topics and sectors addressed include: international convergence; development, public action, and democratic governability; social cohesion and territorial development; employment as the linchpin of the development strategy; the agricultural and livestock sector; industrial integration and competitiveness; energy and development; and international insertion"--P. 24.